Comparatively examining of the apelin-13 levels in the Capoeta trutta (Heckel, 1843) and Cyprinus carpio (Linnaeus, 1758) - Koprucu, S.; Algul, S. (Wiley, 2015)
Apelin is a recently discovered peptide produced by several tissues in the various vertebrates and fish. Apelin has been suggested to have role in regulation of many diverse physiological functions including food intake, energy homoeostasis, immunity, osmoregulation and reproduction. In this study, apelin-13 levels in the blood serum of Cyprinus carpio and Capoetta trutta were determined. Then the results were compared between two species and sexes of each species. Apelin-13 level was analysed using the enzyme-linked immunoassay (ELISA) kit (Rat apelin-13 ELISA kit, catalog no: CSB-E14367r). Apelin-13 level in the blood serum of C. trutta was significantly higher than those of the C. carpio (p < 0.05). However, its levels were observed to be no significant difference (p > 0.05) that compared to between sexes of each species. There was a significant negative correlation (r = -0.829, p = 0.0001) between the apelin-13 level and body weight of C. carpio. However, no significant correlation (r = -0.022, p = 0.924) between the apelin-13 level and weight of C. trutta observed.
Keywords: Apelin; Cyprinus carpio; Capoetta trutta; ELISA